Complementing Mammography Screening with Automated 3D Ultrasound in Women with High-Density Breasts - А. E. Garanina; A. V. Kholin (Вестник рентгенологии и радиологии)
Background. In early breast screening structure, an important factor is breast density. Women with types C and D breast density according to American College of Radiology (ACR) classification have 4–6-fold increased risk of cancer compared to women with type A breast density. With this type of density, the effectiveness of diagnostic mammography (MG) is significantly decreased. Today, automated breast 3D ultrasound can be considered as an additional screening method in women with breast structure types C and D according to ACR.Objective: to perform a comparative analysis of the diagnostic efficacy of 2D and 3D ultrasound in women aged 40 years and older with high breast tissue density.Material and methods. Retro-prospective, observational, single-center study was conducted. From February 2019 to May 2023, 1283 patients aged 40 years and older were examined. The patients were divided into two groups. In group A, women underwent 2D ultrasound and MG. In group B, additionally to these methods, 3D ultrasound was performed. In both groups, the results were evaluated according to Breast Imaging-Reporting and Data System (BI-RADS). Based on the obtained data, the following indicators were determined: positive (PPV) and negative (NPV) predictive values, sensitivity, specificity and accuracy of all methods. For 2D and 3D ultrasound, the predictive model areas under curve (AUC) of receiver operating characteristic (ROC) were calculated.Results. MG method showed PPV 0.89, NPV 0.93, sensitivity 0.53, specificity 0.99, and balanced accuracy 0.76. Indicators for 2D ultrasound demonstrated PPV 0.8, NPV 0.98, sensitivity 0.9, specificity 0.97, balanced accuracy 0.93, AUC ROC 0.968. The results for 3D ultrasound were as follows: PPV 0.97, NPV 0.97, sensitivity 0.9, specificity 0.99, balanced accuracy 0.94, AUC ROC 0.98.Conclusion. The diagnostic efficiency of breast automated 3D ultrasound in patients aged 40 years and older is comparable to 2D ultrasound in terms of sensitivity, and it’s better in terms of accuracy, specificity. The prognostic model of 3D ultrasound is also better compared to 2D ultrasound.